A case series of spinal infections following COVID-19: a delayed complication - Mohamed Ramlee, Fadzrul Abbas; Harun, Mohd Hezery; Nagaretnam, Vinodharan; Teck, Siang Lim; Aris, Hasry Faris; Chor, Ngee Tan (Springer, 2022)
Spinal infection in the form of tuberculous vertebral osteomyelitis or pyogenic spondylodiscitis is a commonly associated state of an immunodeficient host from various pathologies. For example, secondary infections can be seen following coronavirus disease 2019 (COVID-19). We report three cases of different forms of spinal infections that occurred as delayed complications to recent COVID-19 infection. The first case is a 60-year-old female who was diagnosed with an epidural abscess presenting with severe back pain and bilateral lower limb weakness. The second case is an elderly male who was diagnosed with L3/L4 spondylodiscitis and presented with predominantly back pain and minimal leg symptom. The final case is a young female who was diagnosed with severe T5 tuberculous spondylitis and presented with a complete sensory and motor deficit from T5 below. All patients showed good improvement after surgery and antibiotic therapy. Patients treated for COVID-19 are at risk of spinal infection development due to multiple pathophysiologies. Treatment of these various forms of spinal infection remains difficult, and we encourage physicians to be vigilant for the development of these complications post COVID-19 infection.